The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1073/pnas.0912737107
|View full text |Cite
|
Sign up to set email alerts
|

Vaccinia-like cytoplasmic replication of the giant Mimivirus

Abstract: Poxviruses are considered to be unique among all DNA viruses, because their infection cycle is carried out exclusively in the host cytoplasm. Such an infection strategy is of interest, because it necessitates generation of elaborate factories in which viral replication and assembly are promoted. By using diverse imaging techniques, we show that the infection cycle of the largest virus currently identified, the Acanthamoeba polyphaga Mimivirus, similarly occurs exclusively in the host cytoplasm. We further show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
127
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(137 citation statements)
references
References 27 publications
8
127
0
Order By: Relevance
“…However, at variance with Mimivirus where rounded cells remained adherent, Megavirus infection caused most of them to come off their support, making the cultures more difficult to monitor by regular microscopy. A. castellanii cells infected by Megavirus exhibited three distinctive ultrastructural features in succession, as described for Mimivirus (11,14,18). First, the "seed," corresponding to the Megavirus core nucleocapsid extracted from the external particle layers, appeared clearly separated from the cell cytoplasm by a well-delineated lipid membrane ( Fig.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…However, at variance with Mimivirus where rounded cells remained adherent, Megavirus infection caused most of them to come off their support, making the cultures more difficult to monitor by regular microscopy. A. castellanii cells infected by Megavirus exhibited three distinctive ultrastructural features in succession, as described for Mimivirus (11,14,18). First, the "seed," corresponding to the Megavirus core nucleocapsid extracted from the external particle layers, appeared clearly separated from the cell cytoplasm by a well-delineated lipid membrane ( Fig.…”
Section: Resultsmentioning
confidence: 72%
“…This membrane likely derives from the most internal of the two membranes visible inside the virus particles, as expected from the infection process (opening of the stargate, followed by the fusion of the first virus membrane with the vacuole membrane). These seeds then progressively turn into early virion factories recognizable as electron-dense nucleic acid-rich regions (18) isolated from the surrounding cytoplasm by an exclusion zone constituted of a mesh of fibrils 16 nm in diameter ( Fig. 1 E and F).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies revealed that, shortly after the release of the mimivirus genome into the host cytoplasm by the opening of a modified icosahedral capsid vertex, termed the "stargate" (34), initial replication centers are generated (26). Each replication center originates from one infecting virus, as was also demonstrated for the vaccinia virus (27).…”
Section: Resultsmentioning
confidence: 83%
“…With a diameter of 750 nm and harboring about 1,000 genes (25), the mimivirus, which belongs to the Mimiviridae family, represents one of the largest viruses known to date. Notably, the mimivirus infection cycle occurs entirely within the host cytoplasm (12,26), in contrast to other double-stranded DNA (dsDNA) viruses, with the exception of vaccinia virus (8,27) and pithovirus (23). Thus, host nuclei that generally provide optimal platforms for replication of dsDNA viruses (18) do not function as such with these viruses.…”
mentioning
confidence: 99%
“…1). Giant viruses such as APMV and CroV replicate in large cytoplasmic virion factories, and encode an enzymatic complexity that is unrivalled among viruses and includes a presumably complete transcription apparatus, which is packaged in the virion and used to initiate viral gene transcription at the early stage of infection [9][10][11][12] . Although yet to be confirmed experimentally, Sputnik and Mavirus appear to depend on the transcription system of their associated giant viruses, as strongly suggested by the specific promoter and polyadenylation signals that are shared between these virophages and their giant viruses 4,13,14 .…”
mentioning
confidence: 99%